Gauge condition for studying intrinsic magnetospheres. (22nd December 2015) - Mendoza, Miller; Morales, John
Abstract : We propose an analytical model based on the solution of the magnetohydrodynamics (MHD) equations for studying intrinsic magnetospheres. For this purpose, we introduce a new gauge condition for the electromagnetic vector potential, which simplifies the solution of this complex system of nonlinear equations. Using this model, we analyse the deformation of the terrestrial magnetic field due to the presence of the solar wind. By comparing the results with experimental observations, we find that our model reproduces with good agreement the geometrical configuration of the magnetosphere, and that the solar wind should have a finite conductivity. This model could also be used to perform linear stability analysis of fluid and magnetic instabilities. Finally, our solution is not limited to magnetospheric configurations but also applies to a steady-state incompressible and irrotational flow with large plasma parameter and small velocity fluctuations.